Quality characteristics of fermented mushroom and vegetable product using a mixed starter of lactic acid bacteria - Kamonwan Manowan; Pairote Wongputtisin; Unnop Tassanaudom; Tanongsak Sassa- Deepaeng; Ni-orn Chomsri (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
Lactic acid fermentations can be performed through inoculation in orderto ensure consistent product quality and safety. This research investigatesthe effect of the use of Lactobacillus plantarum and Lactobacillusjohnsonii as a mixed starter in mushroom and vegetables fermentation onits product quality. The fermented product showed pH, titratable acidityand total phenolic content of 4.01±0.02, 1.00±0.03% and 519±11 mgGAE/kg respectively. Lactic acid bacteria counts in the fermentedproduct were between 8.5-9.5 log cfu/g throughout the storage time. Theresults from this research suggests quality satisfaction of the fermentedproduct in microbial, chemical and sensory after 30-day storage at 4C.This study showed that the fermented mushroom and vegetable producthas the potential to be used as a probiotic carrier food.